The application of digital health as a nursing solution for leprosy patients during the COVID-19 pandemic: a systematic review - Dahoklory, Dorsina Fransisca; Haryanto, Joni; Indarwati, Retno (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the effect of using digital health technology on leprosy control programmes. Method: The systematic review comprised search on PubMed, Scopus, ScienceDirect, SAGE and ProQuest databases for interventional studies published in English language from 2013 to 2021 which used digital health technology for leprosy contact tracing, active leprosy detection, monitoring of multi-drug therapy and treatment management during the corona virus disease-2019 pandemic A standard risk of bias tool was used to evaluate bias in the studies, and the Joanna Briggs Institute protocol was used to assess the quality of the studies analysed. Results: Of the 205 studies initially identified, 15(7.3%) were analysed in detail. Quasi-experimental studies had a low risk of bias compared to the rest. The e-leprosy framework was being used along with applications based on smartphones and artificial intelligence Digital health technology was found to be practical, accessible and effective in leprosy control programmes. Conclusion: Studies reported favourable findings regarding the use of digital health technology in services related to leprosy patients. Keywords: Prophylaxis, Leprosy, COVID-19, Nursing.